EXISTENCE OF SOLUTIONS FOR HIGHER ORDER MULTI-POINT BOUNDARY VALUE PROBLEM AT RESONANCE - 林晓洁 杜增吉 葛渭高 (Applied mathematics and mechanics, 2006)
Using the theory of coincidence degree, a class of higher order multi-point boundary value problem for ordinary differential equations are studied. Under the boundary conditions satisfying the resonance case, some new existence results are obtained by supposing some conditions to the nonlinear term and applying a priori estimates.